If 3m - 7 = 8, then m = 5
3m + 15 = 45 3m = 30 m = 10
M = 22
mn - 15 + 3m - 5n Rearranging: mn + 3m - 5n - 15 = m(n + 3) - 5(n + 3) = (m - 5)*(n + 3)
m(3m + 2)
If 3m - 7 = 8, then m = 5
3m + 15 = 45 3m = 30 m = 10
6m + 5 = 3m - 4Subtract 3m from each side:3m + 5 = -4Subtract 5 from each side:3m = -9Divide each side by 3:m = -3
The value of m in the equation: 4m-5 = 3m +7 is 12.
3m.
(m + 5)(3m - 1)
3m+2=17 First, subtract 2 to get m on one side. 3m+2-2=17-2 3m=15 Divide by 3 to get m by itself. 3m/3=15/3 m=5 m equals 5.
M = 22
4m + 3m = 180 7m = 180 m = 25 5/7
mn - 15 + 3m - 5n Rearranging: mn + 3m - 5n - 15 = m(n + 3) - 5(n + 3) = (m - 5)*(n + 3)
3m + 7 = 5 Subtract 7 from both sides: 3m = -2 Divide both sides by 3: m = -2/3
It is an equation and the value of m is -6